Web-Based Management System: Luna Yoga - NG JING JING; DR. MUBARAK SAIF MOHSEN AL-ABSI (Applied Information Technology And Computer Science, 2025)
Luna Yoga Management System is a web-based management system for lessening administrative workload with the class management function and financial and reporting function; empowers instructors to facilitate the yoga class while also improving learners’ booking, payment, and communication processes. The system is proposed to solve the overlap booking problem, error-prone when doing accounting analysis, and enhance booking processing time. The methodology of this system is using the Waterfall model. The implementation part of the system uses PHP and HTML programming language with MySQL as the database. With the development of this management system, this system makes yoga class management simpler for the administrator and instructor for scheduling, booking, updating and facilitating yoga and sound bath classes. At the same time, learners can easily book their yoga classes through this online system.